Hieroglyphs of Northern Life: A Book about N.K. Roerich by E.G. Soini - Gracheva, Svetlana M. (Actual Problems of Theory and History of Art, 2024)
Nikolai Konstantinovich Roerich, whose 150th anniversary is widely celebrated in 2024, is one of those artists and thinkers in the history of world culture, about whom countless works have been written by specialists in different fields. These include art historians, philosophers, and experts in esoteric teachings. The article presents a review of Elena G. Soini’s scholarly monograph, “N.K. Roerich: Hieroglyphics of Northern Life” (2022). The author of the research has devoted a big portion of her professional career to the study of N. K. Roerich’s legacy. The book about Roerich is a unique synthesis of philological and art-historian research methodologies applied to the material under study. The work demonstrates the strong influence of the Scandinavian cultural tradition on the formation of Roerich’s personality and worldview. It also reveals the underlying commonality between Roerich’s painting and the Scandinavian National Romantic style.
Keywords: N.K. Roerich; Sortavala; Russian-Finnish artistic ties; Roerich’s anniversary; artistic heritage